Staphylococcus aureus impairs sinonasal epithelial repair: Effects in patients with chronic rhinosinusitis with nasal polyps and control subjects - Valera, Fabiana C.P.; Ruffin, Manon; Adam, Damien; Maillé, Émilie; Ibrahim, Badr; Berube, Julie; Rousseau, Simon; Brochiero, Emmanuelle; Desrosiers, Martin Y. (Journal of allergy and clinical immunology, 2019)
The effect of Staphylococcus aureus on nasal epithelial repair has never been assessed in patients with chronic rhinosinusitis with nasal polyps (CRSwNP). This study aimed to determine whether (1) nasal epithelial cell cultures from patients with CRSwNP and control subjects repair differently; (2) S aureus exoproducts compromise nasal epithelial repair; (3) S aureus alters lamellipodial dynamics; and (4) deleterious effects could be counteracted by the Rho-associated coiled-coil kinase inhibitor Y-27632. Primary nasal epithelial cells (pNECs) collected during surgeries were cultured and injured under 3 conditions: (1) basal conditions, (2) exposed to S aureus exoproducts, and (3) exposed to S aureus exoproducts and Y-27632. Epithelial repair, lamellipodial dynamics, and cytoskeletal organization were assessed. Under basal conditions, pNEC cultures from patients with CRSwNP presented significantly lower repair rates and reduced lamellipodial protrusion length and velocity than those from control subjects. S aureus exoproducts significantly decreased repair rates and protrusion dynamics in both control subjects and patients with CRSwNP; however, the effect of S aureus on cell protrusions was more sustained over time in patients with CRSwNP. Under basal conditions, immunofluorescence assays showed significantly reduced percentages of cells with lamellipodia at the wound edge in patients with CRSwNP compared with control subjects. S aureus altered cell polarity and decreased the percentage of cells with lamellipodia in both groups. Finally, Y-27632 prevented the deleterious effects of S aureus exoproducts on CRSwNP repair rates, as well as on lamellipodial dynamics and formation. S aureus exoproducts significantly alter epithelial repair and lamellipodial dynamics on pNECs, and this impairment was more pronounced in patients with CRSwNP. Importantly, Y-27632 restored epithelial repair and lamellipodial dynamics in the presence of S aureus exoproducts. [Display omitted]